Philanthropy and Global Warming: The Potential of Green Waqf in Addressing Climate Change in Indonesia - Saputro, M. Bagus; Zahro', Khurun'in; Syahruddin, Syahruddin; Cahyo, Eko Nur (UNISSULA, 2025)
Indonesia, with its vast tropical rainforests, faces serious threats such as illegal logging and forest fires that exacerbate greenhouse gas emissions and environmental degradation. Amid this crisis, Green Waqf emerges as an innovative solution that leverages philanthropy for environmental conservation. This research examines the potential of Green Waqf in supporting forest conservation, carbon emission reduction, and climate change mitigation in Indonesia. The primary focus is on exploring the integration of Green Waqf with conservation efforts and the social and environmental benefits it offers, as well as identifying challenges and opportunities in its implementation. The methodology employed a qualitative, library-based approach, which enabled the author to verify prior research findings and contribute new elements. Descriptive analysis was used to provide an in-depth understanding of related theories and experts' views. The findings indicate that Green Waqf can be an effective tool for mitigating climate change through forest conservation projects, tree planting, and resource management. In addition to reducing carbon emissions, Green Waqf also provides social benefits by creating local economic opportunities and enhancing community welfare.